Building Urban Resilience : An Evaluation of the World Bank Group's Evolving Experience (2007-2017) - Independent Evaluation Group (World Bank, Washington, DC, 2019)
This evaluation examines the World Bank Group’s evolving experience in building resilience in urban areas during the period 2007–17. The focus of this evaluation is the World Bank Group’s support to clients in building urban resilience—to cope, recover, adapt and transform—in the face of shocks and chronic stresses.